"Imprinting" Catalytically Active Pd Nanoparticles onto Ionic‐Liquid‐Modified Al2O3 Supports. Issue 8 (18th April 2013) - Luza, Leandro; Gual, Aitor; Eberhardt, Dario; Teixeira, Sérgio R.; Chiaro, Sandra S. X.; Dupont, Jairton
<x xml:space="preserve">Abstract</x> Going against tradition: Uniformly distributed Pd nanoparticles on imidazolium‐ionic‐liquid‐modified Al2O3 surfaces are prepared by a top down approach by using a new sputtering chamber. The hydrogenation of 1, 3‐cyclohexadiene is used to probe the surface properties of these new Pd nanoparticles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>